National Solid Waste Policy: analysis of final disposal in Teófilo Otoni/MG and the surrounding area (International Journal of Geoscience, Engineering and Technology, 2025)
This article examines the effectiveness of the National Solid Waste Policy (PNRS), established by Law n°. 12,305/2010, in municipalities with high socioeconomic vulnerability in the semi-arid region of Minas Gerais. The focus is on Teófilo Otoni and neighboring areas in the Mucuri Valley. The study uses a literature review and analyzes secondary data from official sources, including the IBGE. The results reveal several problems: the continuous existence of uncontrolled landfills, limited structured public policies, weak implementation of Municipal Integrated Solid Waste Management Plans (PMGIRS), and a lack of effective inter-municipal cooperation. Furthermore, the analysis highlights fragmented governance and inadequate technical and financial support for smaller municipalities. Although the PNRS represents a significant regulatory advancement, its implementation in peripheral regions is limited by structural and operational challenges. The study suggests that strengthening inter-municipal partnerships, promoting inclusive recycling practices, and ensuring sufficient funding mechanisms are vital to improving the policy's effectiveness at the local level.